Experimental studies and mathematical modeling of the curing reaction of bioinspired copolymers. Issue 4 (2nd October 2018) - Chen, N.; Lee, N.; Bortolato, S. A.; Martino, D. M.
ABSTRACT: Polymer curing is a complex process that significantly delineate the final properties of the synthetized material. In this work, the photo-induced crosslinking reaction of synthetic "bio-inspired" copolymers based on thymine and ionic groups was studied by gel permeation chromatography and UV absorption spectroscopy. A mathematical model for the curing process based on statistical techniques and coupled to the kinetics of crosslinking was developed. The model allows to predict both, the evolution of the crosslinking degree as a function of curing time and the gel times as a function of the molecular structure of the copolymer and the curing conditions. The theoretical values showed a very good agreement with the UV–Vis and GPC spectroscopy experimental results for all the copolymers studied. A better knowledge of the curing kinetics of thymine-based biopolymers will enable to develop materials with pre-specified properties and to improve their applications. GRAPHICAL ABSTRACT: